Improving character Based Writing by Applying Think Pair Share Method - Tri Rejeki; Hersulastuti NA; Umi Sholihah (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2019)
The data of this study are student activities and learning outcomes writing using Think Pair Share method. This research method is classroom action research. The subjects of this study were students in X IPA 6 of SMA Muhammadiyah 1 Klaten. Which consists of two cycles, each cycle consists of two meetings. The purpose of this study was Think Pair Share model to increase activity and learning outcomes. The use of analytic research describes data analysis. Before the acting class research conducted in the pre-test was 16%, the increase in cycle 1 was 52% and 84% in the second cycle. That the application of think pair share model of student learning outcomes can, as evidenced by an increase in learning outcomes showed an increase in student scores 4.6 (71.8 - 67.2) from test one.In addition, the results of this study also experienced an increase in character in every aspect, namely responsibility, confidence, honesty, cooperation, good communication, and others. This can be seen in activities in cycles 1 and 2. The results show that the results of Think Pair Share can improve the character and learning outcomes in X IPA 6 of SMA Muhammadiyah1 Klaten in the academic year of 2017/2018.